Escazu agreement: challenges regarding its ratification in colombia - Mesa Neira, Alejandro (2022)
On March fourth of 2018 the Escazu Agreement was adopted, which first emerged on the United Nations Conference of Sustainable Development, also known as Rio + 20. The purpose of this agreement is to guarantee the full implementation of the rights to public participation in environmental decision-making processes, access to environmental information and access to justice.This paper analyzes the implications that ratifying the Escazu Agreement would cause in Colombia, in order to determine the impact of its implementation in the legal system.